Integral Europe : Fast-Capitalism, Multiculturalism, Neofascism. - Holmes, Douglas R. (Princeton University Press, 2011)
Over the past 15 years, the project of advanced European integration has followed a complex secular and cosmopolitan agenda. As that agenda has evolved, however, so have various hard-line populist movements with goals diametrically opposed to the ideals of a harmonious European Union. Spearheaded by figures such as Jean-Marie Le Pen, the controversial leader of France's National Front party, these radical movements have become increasingly influential and, because of their philosophical affinities with fascism and national socialism--politically worrisome. In Integral Europe, anthropologist Dou.